The 2nd International Electronic Conference on Water Sciences 2017
DOI: 10.3390/ecws-2-04954
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Microbial Risk Assessment (QMRA) of Campylobacter for Roof-Harvested Rainwater Domestic Use

Abstract: Abstract:The present study evaluated the microbiological risk for roof-harvested rainwater (RHRW), with Campylobacter as the pathogenic microorganism of reference, using a Quantitative Microbial Risk Assessment (QMRA). QMRA has been widely used as an alternative method for epidemiological assessment of human exposure to microorganisms that can cause diseases, through a four-step process: hazard identification, exposure assessment, dose-response assessment, and risk characterization. The results presented drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Quantitative Microbial Risk Assessment (QMRA) is an effective methodology to estimate the risk of infectious diseases. QMRA has been utilized to investigate the inhalation health risk of pathogens generated from reused water 10,11 and waste management facilities for livestock farms. 12,13 Recently, the QMRA method has been adopted to investigate the airborne infection risk of MERS-CoV in a hospital, which indicated that the daily mean risk of infection for the nurses and healthcare workers was relatively high (>10 −4 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative Microbial Risk Assessment (QMRA) is an effective methodology to estimate the risk of infectious diseases. QMRA has been utilized to investigate the inhalation health risk of pathogens generated from reused water 10,11 and waste management facilities for livestock farms. 12,13 Recently, the QMRA method has been adopted to investigate the airborne infection risk of MERS-CoV in a hospital, which indicated that the daily mean risk of infection for the nurses and healthcare workers was relatively high (>10 −4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative Microbial Risk Assessment (QMRA) is an effective methodology to estimate the risk of infectious diseases. QMRA has been utilized to investigate the inhalation health risk of pathogens generated from reused water , and waste management facilities for livestock farms. , Recently, the QMRA method has been adopted to investigate the airborne infection risk of MERS-CoV in a hospital, which indicated that the daily mean risk of infection for the nurses and healthcare workers was relatively high (>10 –4 ) . Atmospheric dispersion models were utilized in the QMRA studies for foot-and-mouth-disease virus, avian influenza virus, , Legionella , the spore-forming bacterium B.anthracis , and the C. burnetii bacterium for Q fever. , The atmospheric dispersion models estimate the temporal and spatial distribution of hazardous pollutants for a large scale and long period, which is difficult to achieve by field sampling and measurements. Biologic decays were normally included in the models …”
Section: Introductionmentioning
confidence: 99%
“…A member of this group M. gordonae was found in one out of 8 analysed samples. In the literature Salmonella has been reported in 4-10% of roof rainwater samples from stormwater tanks and Campylobacter in 3-40.7% of roof harvested rainwater samples (2,15). Other studies have reported the presence of Mycobacterium avium in 17.2% of samples and Mycobacterium intracellulare in 78.4% of rainwater samples from a total of 134 samples tested (2).…”
Section: Discussionmentioning
confidence: 99%
“…Other factors, like roof material, physical boundary conditions, location, precipitation event characteristics, local meteorological factors, chemical properties, and so on, are likely to influence rainwater quality (Forster 1998). But simple systems to dodge the first flush (1-2 mm of rain) are enough to clean the roof and only the fraction of the water to drink can be filtered and disinfected and used (Hora et al 2017). This is a popular practice in Australia and in the Brazilian semi-arid where 1 million systems were installed in one decade.…”
Section: Introductionmentioning
confidence: 99%